PENCEGAHAN ISPA MELALUI METODE EMO-DEMO DI KELURAHAN PASAR AMBACANG - fuji nurzahirah; Erick Zicof; Widdefrita Widdefrita; Nindy Audia Nadira; John Amos (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2025)
Background: Acute Respiratory Infection (ARI) remains one of the major public health problems in Indonesia. In Padang City, ARI ranks first among the most prevalent diseases, with a proportion of 25.7%. Based on the report from Pasar Ambacang Public Health Centerduring the period of January–November 2024, there were 3,092 recorded cases of ARI. The high incidence is partly due to the lack of public knowledge regarding ARI prevention efforts. Objective: This study aimed to determine the differences in community knowledge and attitudes regarding ARI prevention efforts using the Emo-Demo method. Methods: This study employed a mixed-method design. The qualitative approach used an exploratory case study design with in-depth interviews involving community members, the ARI program manager, a design expert, an Emo-Demo expert, and a linguist. The quantitative approach applied a quasi-experimental design with a one-group pre-test and post-test approach. The study was conducted in Pasar Ambacang Sub-district from November 2024 to May 2025, with a total sample of 63 respondents. Results: The findings indicated an improvement in community knowledge after the Emo-Demo intervention. The average knowledge score increased from 4.33 before the intervention to 8.00 afterward. Similarly, the average attitude score increased from 39.87 before the intervention to 43.84 after the intervention. Statistical tests showed a significant difference in knowledge (p-value = 0.0001) and attitude (p-value = 0.0001) before and after the intervention. Conclusion: The Emo-Demo method was proven effective in improving community knowledge and attitudes toward ARI prevention in Pasar Ambacang Sub-district.